ChemInform Abstract: The First Fe‐Based Na+‐Ion Cathode with Two Distinct Types of Polyanions: Fe3P5SiO19. Issue 34 (August 2015) - Kan, W. H.; Huq, A.; Manthiram, A.
Abstract Fe3P5SiO19 is prepared by calcination of stoichiometric amounts of FePO4, SiO(OH)2, and NH4H2PO4 in air (1000 °C, 12 h).